2018
DOI: 10.1155/2018/2314769
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Effect of Nonalcoholic Fatty Liver Disease and Metabolic Syndrome on Osteoporosis in Postmenopausal Females in Eastern China

Abstract: The present study evaluated the potential combined effects of NAFLD and MetS on the development of osteoporosis. The relationship between NAFLD and MetS and osteoporosis was assessed in 938 postmenopausal female participants. Moderate and severe NAFLDs were combined as significant NAFLD (SNAFLD). All the subjects were divided into 4 subgroups based on the status of SNAFLD and MetS. Relative excess risk of interaction (RERI), attributable proportion (AP) of interaction, and synergy index (SI) were used to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 55 publications
2
25
0
2
Order By: Relevance
“…A retrospective study among Taiwanese population [n=2007, aged > 50 years] also reported no association between MetS and osteoporosis in both sexes [57]. In contrast, Chen et al [58] showed that both MetS and non-alcoholic fatty liver disease associated with it were positively associated with osteoporosis among postmenopausal women from Eastern China [n=938, aged 61.2 (SD 13.8) years].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study among Taiwanese population [n=2007, aged > 50 years] also reported no association between MetS and osteoporosis in both sexes [57]. In contrast, Chen et al [58] showed that both MetS and non-alcoholic fatty liver disease associated with it were positively associated with osteoporosis among postmenopausal women from Eastern China [n=938, aged 61.2 (SD 13.8) years].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study by Chen et al reported that both MetS and the associated non-alcoholic fatty liver disease were positively associated with osteoporosis among Chinese post-menopausal women (n=938). 24 The negative relationship was further consolidated in cross-sectional studies. Hwang and Choi reported that the lumbar spine BMD adjusted for age, weight and height decreased with increasing MetS components in Korean adult women (n=2548).…”
Section: Negative Association Between Mets and Bone Mineral Densitymentioning
confidence: 96%
“…A retrospective study by Chen et al reported that both MetS and the associated non-alcoholic fatty liver disease were positively associated with osteoporosis among Chinese post-menopausal women (n=938). 24 …”
Section: Relationship Between Mets and Bone Mineral Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…Less is known about non-alcoholic fatty liver disease (NAFLD) or non-alcoholic steatohepatitis (NASH). The mean prevalence of HOD in this patient group, often composed of children, is reported to be 45.7% [22,23,24]. Approximately every second patient (49.3%) with hemochromatosis shows altered bone structure (osteopenia or osteoporosis) [25,26,27].…”
Section: Hepatic Osteodystrophy—definition and Prevalencementioning
confidence: 99%